2018
DOI: 10.21037/jgo.2018.09.06
|View full text |Cite
|
Sign up to set email alerts
|

Novel use of proton beam therapy for neoadjuvant treatment of radiation-associated squamous cell carcinoma of the esophagus

Abstract: Secondary esophageal cancers from prior thoracic radiation therapy are rare but challenging cases to deliver standard combined modality therapy as part of a curative approach. In patients with prior exposure to cardiopulmonary-toxic chemotherapy or radiotherapy, management requires meticulous multidisciplinary evaluation given the morbidity associated with surgery in the previously irradiated thorax and re-irradiation of the spinal cord, heart, and lungs. Oftentimes, suboptimal treatment regimens, either with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…[33][34][35][36][37][38][39][40][41] For breast cancer specifically, small series have described significantly reduced cardiac and pulmonary exposures when RT is delivered with photons compared with protons, with particular emphasis on cardiac structures. [20][21][22]42 However, clinicians and national clinical trial protocols 43 continue to base RT planning goals (and, by extrapolation, plan quality) on historical photon constraints. Although it is widely accepted that PBT plans should meet, if not significantly improve, on classical photon dose constraints, new target ranges have not been established.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40][41] For breast cancer specifically, small series have described significantly reduced cardiac and pulmonary exposures when RT is delivered with photons compared with protons, with particular emphasis on cardiac structures. [20][21][22]42 However, clinicians and national clinical trial protocols 43 continue to base RT planning goals (and, by extrapolation, plan quality) on historical photon constraints. Although it is widely accepted that PBT plans should meet, if not significantly improve, on classical photon dose constraints, new target ranges have not been established.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,37,38 A contemporary propensity score-matched analysis was more promising and has suggested survival benefit from re-RT, which may reflect the increasing precision of RT in the modern era. 7 To date, series describing re-RT delivered with proton radiation are even more scarce and smaller, 2,4,8 and the only form of prospective data examining re-RT for locoregionally recurrent esophageal þ GEJ cancers comes from an updated singleinstitutional analysis of 14 patients that revealed feasibility of proton re-RT delivery, but with a 35.7% rate of G3 or higher toxicities. 2,8 Our in silico dosimetric comparison is in agreement with previously described dosimetric literature and supports the suggestion that when re-RT is undertaken, proton radiation should be strongly, if not exclusively, considered when available.…”
Section: Discussionmentioning
confidence: 99%
“…A paucity of data exists to guide re-RT dosing for either de novo or recurrent esophageal þ GEJ malignancies and associated techniques, with treatment being nonstandardized. Published data are either limited by small sample size [2][3][4] or focused primarily on photon radiotherapy, 5 often describing a high rate of severe (grade 3 [G3]) late treatment-related toxicities. 2,6 In the modern era, with more contemporary treatment techniques, studies have reported a survival benefit when recurrent esophageal cancers are treated with radiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Late grade ≥3 toxicities included grade 3 dysphagia (n=1, 7%), esophageal stenosis (n=1, 7%), esophageal ulcer (n=1, 7%), heart failure (n=1, 7%), and grade 5 esophageal ulcer (n=1, 7%, favored to be due to LR/persistence rather than PBT). Patel et al (41) present a retrospective case series of 3 patients who received thoracic RT as part of treatment for prior malignancies and subsequently developed esophageal squamous cell carcinoma (SCC), for which they underwent PBT re-irradiation. The first patient previously received involved-field RT to a dose of 36 Gy with 6 cycles of R-CHOP for mediastinal diffuse large B-cell lymphoma, in addition to additional systemic therapy and stemcell transplant, complicated by pulmonary fibrosis and cardiomyopathy.…”
Section: Esophageal Cancermentioning
confidence: 99%